2010
DOI: 10.1073/pnas.1004368107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic suppression of the circadian Clock mutation by the melatonin biosynthesis pathway

Abstract: Most laboratory mouse strains including C57BL/6J do not produce detectable levels of pineal melatonin owing to deficits in enzymatic activity of arylalkylamine N-acetyltransferase (AANAT) and Nacetylserotonin O-methyl transferase (ASMT), two enzymes necessary for melatonin biosynthesis. Here we report that alleles segregating at these two loci in C3H/HeJ mice, an inbred strain producing melatonin, suppress the circadian period-lengthening effect of the Clock mutation. Through a functional mapping approach, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 53 publications
0
31
1
Order By: Relevance
“…In these animals, locomotor activities were increased in response to novel stimuli yet overall activity in the home cage was decreased (40). It is challenging to report that the Clock mutation phenotype can be suppressed by melatonin (or the melatonin agonist, ramelteon) to stabilize circadian rhythms (41).…”
Section: Psychotropic Drug Effects On Clock Genesmentioning
confidence: 99%
“…In these animals, locomotor activities were increased in response to novel stimuli yet overall activity in the home cage was decreased (40). It is challenging to report that the Clock mutation phenotype can be suppressed by melatonin (or the melatonin agonist, ramelteon) to stabilize circadian rhythms (41).…”
Section: Psychotropic Drug Effects On Clock Genesmentioning
confidence: 99%
“…Similarly, timed application of melatonin can entrain blind human subjects (Arendt & Broadway 1987, Sack et al 2000. In vitro, melatonin application to cultured SCN explants affects amplitude and phase of the circadian rhythm of neuronal firing (Liu et al 1997, Shimomura et al 2010. The acute inhibitory effect of melatonin on neuronal activity seems to be mediated by MT1 receptor (Liu et al 1997), while the phase-resetting effect relies on MT2 receptor signalling (Hunt et al 2001).…”
Section: Melatoninmentioning
confidence: 99%
“…Clock-D19 mutants (Vitaterna et al 1994) were back-crossed into a melatonin-proficient strain, showing that the Clock-D19 mutation leads to phase delays and dampening of the melatonin rhythm in constant darkness conditions while GC rhythms were completely abolished (Kennaway et al 2003(Kennaway et al , 2006. More recently, it has been demonstrated that the melatonin biosynthesis pathway can genetically suppress the circadian perturbations of Clock-D19 mutation (Shimomura et al 2010), suggesting a role of melatonin in contributing to the robustness of the SCN clock (see below). PER1 deficiency has been shown to enhance Aanat transcription, enzymatic activity and hence melatonin secretion (Chen & Baler 2000, Christ et al 2010.…”
Section: Scn-pineal Interactionmentioning
confidence: 99%
“…The connections between molecules show molecular interactions identified in the JuB -insomnia interactome. Gene expression illustrated in coloured nodes was selected with a p < 0.05 value Insomnia is the most common sleep disturbance with difficulty initiating or maintaining sleep, along with impaired daytime function (Shimomura, 2010). There is a high prevalence of insomnia in a variety of negative consequences.…”
Section: Discussionmentioning
confidence: 99%